The role of heat shock proteins in reproductive system development and function - MacPhee, Daniel J. (Springer, 2020)
Due to the paucity of reviews on this subject, this volume aims to be timely and promote additional basic and translational research on these proteins in reproductive system development and function within the fields of Anatomy, Embryology and Cell Biology. The breadth of the work being conducted within Reproduction is exemplified by the contributors to this series who will provide reviews on: Grp78 roles in female reproduction, small heat shock proteins/co-chaperones as players in uterine smooth muscle function, the role of heat shock proteins in sperm function and maternal contribution to oogenesis and early embryogenesis, heat shock factors and testes development, HSP90 in ovarian biology and pathology, and the role of HSP70 in regulation of autophagy in pregnancy and parturition.